2009
DOI: 10.1094/phyto-99-5-0487
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Sterol Demethylation Inhibitor-Resistant Isolates of Fusarium asiaticum and F. graminearum Collected from Wheat in China

Abstract: Fusarium asiaticum and F. graminearum are the primary causal agents of Fusarium head blight (FHB) of wheat in China. In this study, sensitivities of 159 F. asiaticum and F. graminearum isolates to a benzimidazole fungicide carbendazim (MBC) and to sterol demethylation inhibitors (DMIs) tebuconazole and prochloraz were determined. Among the 159 isolates, 9 were resistant to MBC and designated as MBC-R isolates. Three showed resistance to tebuconazole and prochloraz and designated as DMI-R isolates. There was no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
116
1
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(124 citation statements)
references
References 27 publications
4
116
1
3
Order By: Relevance
“…Contrastingly, Klix et al (2007), assessed fungicide sensitivity of F. graminearum isolates, based on the ascosporic germination rate, and observed a larger decline in sensitivity over time (1987 to 2004) for tebuconazole, followed by metconazole and prothioconazole. In China, Yin et al, (2009) assessed sensitivity of 40 F. graminearum isolates to tebuconazole and found a EC 50 mean of 0.248 mg/L (0.021-1.152 mg/L), which is much higher than those found in our study to both fungicides tested. However, in Japan, Tateishi et al (2010) studied 101 isolates representing F. graminearum and F. asiaticum populations and found that 80% of isolates showed EC 50 towards metconazole of less than 0.1mg/L, a level of sensitivity more similar to that found in the present study.…”
contrasting
confidence: 73%
See 1 more Smart Citation
“…Contrastingly, Klix et al (2007), assessed fungicide sensitivity of F. graminearum isolates, based on the ascosporic germination rate, and observed a larger decline in sensitivity over time (1987 to 2004) for tebuconazole, followed by metconazole and prothioconazole. In China, Yin et al, (2009) assessed sensitivity of 40 F. graminearum isolates to tebuconazole and found a EC 50 mean of 0.248 mg/L (0.021-1.152 mg/L), which is much higher than those found in our study to both fungicides tested. However, in Japan, Tateishi et al (2010) studied 101 isolates representing F. graminearum and F. asiaticum populations and found that 80% of isolates showed EC 50 towards metconazole of less than 0.1mg/L, a level of sensitivity more similar to that found in the present study.…”
contrasting
confidence: 73%
“…In Europe and Asia, the increasing usage of triazoles in FHB management is suspected to have led to selection of less sensitive isolates of F. graminearum (Klix et al, 2007;Yin et al, 2009;Becher et al, 2010). Fungal resistance to triazoles is associated with mutations in the 14-α-demethylase (CYP51) gene and overexpression of the ATPbinding cassette transporters (Ma and Michailides, 2005;Liu et al, 2010).…”
mentioning
confidence: 99%
“…Para o manejo da giberela e das micotoxinas nos grãos, é recomendado o uso de cultivares com maior grau de resistência, aplicação de fungicidas e o ajuste dos mecanismos da colheita mecânica para a eliminação de grãos giberelados (McMULLEN et al, 2012). Fungicidas do grupo dos triazóis, que possuem ação fungistática sobre F. graminearum sensu lato, têm sido indicados para uso durante o fl orescimento pleno (YIN et al, 2009). Considerando que grãos giberelados são menores e mais leves do que grãos sadios, especialmente aqueles infectados no início do fl orescimento, o ajuste dos mecanismos da colheita mecânica pode facilitar a eliminação de grãos giberelados e, consequentemente, reduzir os níveis de micotoxinas nos lotes de grãos colhidos (SALGADO et al, 2011).…”
Section: Introductionunclassified
“…A few reports 30) have investigated the sensitivity to DMIs and FHB pathogen species but no report has examined the relationship between DMI sensitivity and trichothecene chemotype. Nor has any paper investigated the relationship between the efficacy of DMI and the sensitivity of FHB causal fungi to DMI.…”
Section: Introductionmentioning
confidence: 99%